Applications of Fracture Mechanics in Failure Prevention - W. J. Langford (Canadian Institute of Mining, Metallurgy and Petroleum, 1976)
"Conventional design criteria assume that the fracture strength of a structural material exceeds its yield strength. Fracture below the design load is not expected, y et many structures have failed in this way. The causes of the fractures are almost always discontinuities such as cracks and welding defects. Linear Elastic Fracture Mechanics (LEFM or simply 'fracture mechanics') provides an analytical framework for assessing the influence of sharp defects on the load-bearing capability of a structure. Fracture mechanics techniques have reached the point of acceptance by ASME Design Codes for nuclear components, and ASTM Standards now include well-defined rules for measuring fracture toughness. Starting with a simple equation which relates applied stress and crack size, the influence of the material's thickness and yield strength can be calculated. Thus, the size of defect which will cause failure under the applied stress may be determined. Armed with this information, the metallurgist can assess the safety of a structure from the viewpoints of non-destructive testing standards, construction standards and conditions of operation throughout its service life."